2019
DOI: 10.1186/s12913-019-4080-7
|View full text |Cite
|
Sign up to set email alerts
|

Priorities and challenges for health leadership and workforce management globally: a rapid review

Abstract: Background Health systems are complex and continually changing across a variety of contexts and health service levels. The capacities needed by health managers and leaders to respond to current and emerging issues are not yet well understood. Studies to date have been country-specific and have not integrated different international and multi-level insights. This review examines the current and emerging challenges for health leadership and workforce management in diverse contexts and health systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
153
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(164 citation statements)
references
References 73 publications
2
153
0
9
Order By: Relevance
“…Nowadays health care systems around the world face with several challenges such as increased healthcare needs and costs as a result of growing population that are aging with disability; rising levels of risk factors such as obesity and physical inactivity; poor management and increasing prevalence of chronic disease and multiple chronic diseases; high percentage of preventable hospitalisation as a result; health workforce shortages and imbalanced distribution, and poor quality and safety of service provision [1][2][3]. In addition, inequities in health, lack of access to quality health care, and insufficient skilled health workforce represent some of the major challenges facing many countries in the Eastern Mediterranean Region [4].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays health care systems around the world face with several challenges such as increased healthcare needs and costs as a result of growing population that are aging with disability; rising levels of risk factors such as obesity and physical inactivity; poor management and increasing prevalence of chronic disease and multiple chronic diseases; high percentage of preventable hospitalisation as a result; health workforce shortages and imbalanced distribution, and poor quality and safety of service provision [1][2][3]. In addition, inequities in health, lack of access to quality health care, and insufficient skilled health workforce represent some of the major challenges facing many countries in the Eastern Mediterranean Region [4].…”
Section: Introductionmentioning
confidence: 99%
“…Studies overseas, especially in developed countries, the well-published biggest challenges to senior managers are more on quality and safety related issues rather than issues of conflicts with patients and communication [33]. However, the study identified that the difficulties facing Chinese senior hospital managers are consistent with managers in other countries, including inadequate employee performance evaluation systems [33].…”
Section: Difficulty Encounteredmentioning
confidence: 95%
“…Studies overseas, especially in developed countries, the well-published biggest challenges to senior managers are more on quality and safety related issues rather than issues of conflicts with patients and communication [37]. However, the study identified that the difficulties facing Chinese senior hospital managers are consistent with managers in other countries, including inadequate employee performance evaluation systems [37]. The advancement of medical technology has changed the way how providers practice medicine today and will continue to do so in the foreseeable future.…”
Section: Difficulties Encounteredmentioning
confidence: 99%